Barriers to the adoption of social networking sites in Saudi Arabia's higher education - Alqahtani, S.; Issa, Tomayess (Brill, 2018)
© 2018 Informa UK Limited, trading as Taylor & Francis Group Social networking sites are increasingly being repurposed as academic tools in higher education institutions. In this context, social networking sites are used to support a number of key academic functions, including the sharing of ideas between students and academic staff, the forming of dedicated study groups, the exchange of links and other academic objects and self-publication. While these tools are readily being adopted in mainstream Western contexts, little is currently known regarding whether – and how – social networking sites are used in other geo-cultural regions. This study sought to redress this research gap by investigating what might constitute barriers to the adoption of social networking in higher education in Saudi Arabia from the students’ perspective. The study was based on the analysis of results derived from focus group discussions with university students at four Saudi Arabian universities. The research found that Saudi Arabian students are aware of, and welcome, social networking sites and are starting to use them for academic purposes in the same way that university students do in more mainstream contexts. However, the study did identify a range of barriers to uptake as highlighted by focus group participants.